Proportion of Cancer Deaths Occurring in Hospital, Canada, 1994–2000 - Neutel, C. Ineke (Can J Public Health, 2005)
BACKGROUND: Most terminally ill cancer patients would prefer not to die in hospital, but only a minority achieve their wish. Our objective was to examine the proportion of cancer deaths occurring in Canadian hospitals. METHODS: The two sources of data (1994–2000) were: 1) all hospital separations (HS) with a primary diagnosis of cancer and discharge as ’dead’; 2) all death certificates (DC) with cancer as underlying cause of death. Proportions of hospital deaths were estimated with two different numerators: 1) hospital cancer deaths from HS data, and 2) deaths with hospital as location from DC data; the denominator for both were all cancer deaths identified from the DC data. RESULTS: Proportions of hospital deaths from HS data decreased from 55% to 40% over 1994–2000, was slightly lower for females, decreased with age, but varied widely among provinces. Proportions of hospital deaths from DC data started at 80% and showed a small downward trend over the years. While age, sex, and cancer site distributions stayed the same, the proportion of hospital deaths from DC date again varied among provinces. For provinces with the home category completed on the DC data, 1999–2000, Alberta had most home deaths at 15.6% and PEI least at 5.7%. INTERPRETATION: This is the first Canada-wide data on place of death for terminal cancer, which is important for determining and comparing present-day practices, as well as for planning for the future.